La oncocercosis equina asociada con el mal de la cruz en Colombia : descripción de dos casos - Mullenaux, Charles H; Adams, L. Garry (1971)
Two cases of equine fistolous withers were diagnosed in which Onchocerca sp. was found to be present in the affected tissues. One of the horses had a brucellosis antibody titer of 1:50 using the rapid plate agglutination method and, in the same animal, Brucella sp. was cultured from the suppurative material of the nuchal bursitis of the withers. Macroscopic and microscopic pathological lesions caused by the nematodes Onchocerca sp. were described